Composition and Biological Properties of Agaricus bisporus Fruiting Bodies – a Review - Muszyńska, Bożena; Kała, Katarzyna; Rojowski, Jacek; Grzywacz, Agata; Opoka, Włodzimierz (Polish journal of food and nutrition sciences, 2017)
White is both the most popular and the most commonly eaten edible mushroom species in the world. It is popular not only because of its taste, but also due to its high level of nutrients: dietary fiber (chitin), essential, semi-essential amino acids, unsaturated fatty acids including linoleic and linolenic acids, easily digestible proteins, sterols, phenolic and indole compounds, and vitamins − especially provitamin D and B , B , B , B , and C. Fruiting bodies of have antioxidant, antibacterial, anti-inflammatory, antitumor, and immunomodulatory activity. The presence of antioxidant ergothioneine (which also displays the antimutagenic, chemo- and radioprotective activity) is also noteworthy. also contains derivatives of benzoquinone, a substance which belongs to the group of antibiotics. Studies of tyrosinase isolated from this species show its very high similarity to human tyrosinase. This points directly to the fact that this species could be a rich source of tyrosinase used for medicinal and cosmetics purposes. is also a rich source of selenium, zinc and other elements such as magnesium, copper, iron, potassium, sodium, calcium, phosphorus, sulfur or manganese. In conclusion, the presence of these compounds and elements with biological activity in fruiting bodies of confirms their nutraceutical and medicinal properties.